Turnover Intention’s Employees Retail: The Role Performance And Work Engagment - Alfriano Tri Maulino; Alvin Eryandra (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2024)
This study aims to determine the effect of employee performance and work engagement on turnover intention both partially and simultaneously at retail organization. This research uses a quantitative approach. The sampling used is accidental sampling through google form with a total of 496 respondents of retail organization employees. Employee performance measurement tools are measured by the Individual Work Performance Questionnaire (IWPQ) of 18 items. Work engagement is measured by the Utrecht Work Engagement Scale-9 (UWES-9) with a total of 9 items. Turnover intention was measured by Turnover Intention Scale (TII) by Mobley with 3 items. Data were processed using Jamovi 2.4 software with multiple linear regression models. Hypothesis testing results show that employee performance has no effect on turnover intention. While the work engagement variable has a negative effect on turnover intention. Simultaneously, employee performance and work engagement positively affect turnover intention by 6.7%.